Information Literacy of First-Year Undergraduates Across Disciplines - Engineering, Architecture, and Information Technology - Wickramasinghe, Vathsala; Seneviratne, Thushari (Edulib, 2022)
The literature suggests that students commence university education with limited levels of IL, and this is true for both developed and developing countries. When universities understand entry-level students’ actual level of IL at the beginning of their undergraduate programmes, universities can objectively describe entry-level undergraduates’ IL levels and take steps to improve the levels to match with required revels for academic success. The purpose of the study was to investigate the information literacy of first-year undergraduates of engineering, architecture, and information technology disciplines when they commence their university education, and whether socio-demographic characteristics are associated with the information literacy of first-year undergraduates. 545 first-year undergraduates covering the three study disciplines responded to the survey questionnaire. Quantitative methods were used to analyse the data. Findings revealed that although information literacy exists in undergraduates to a certain extent, these vary by the discipline of study. The findings imply the need of addressing information literacy requirements by the discipline of the study to better serve undergraduates. Overall, the results lead to understanding information skills and behaviour of entry-level undergraduates, and what kinds of library services are appropriate and necessary for undergraduates across disciplines.